HUBUNGAN ANTARA KEBIASAAN BELAJAR DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR MATEMATIKA SISWA SMP SELAMA PEMBELAJARAN DARING - Mahmudah, Khoirotul; Pambudi, Didik Sugeng; Oktavianingtyas, Ervin; Lestari, Nurcholif Diah Sri; Murtikusuma, Randi Pratama (Department of Mathematics Education , University of Jember, 2021)
The purpose of this study was to determine the correlation between study habits and mathematics learning outcomes, the correlation between learning motivation and mathematics learning outcomes, and the correlation between learning habits and motivation to learn mathematics outcomes during online learning. The total population is 185 students and the sample size is 123 students with the sampling technique using the Slovin formula approach. Hypothesis testing using multiple regression analysis techniques, Pearson Correlation test, F test, and a coefficient of determination of 5%. Learning habits and motivation are measured by a questionnaire that has been declared valid by the validator and has been tested for validity and reliability on 60 respondents outside the research subject. Data collection to measure learning habits and motivation is done by distributing questionnaires, while for student achievement it is obtained from documentation of math scores. The results showed that: there was a positive and significant correlation between study habits and students' mathematics learning outcomes. The correlation between the two is moderately correlated; there is a positive and significant correlation between learning motivation and student outcomes in mathematics. The correlation between the two is strongly correlated; there is a positive and significant correlation between study habits and learning motivation with students' mathematics learning outcomes. The correlation between the two is strongly correlated. The contribution of study habits and learning motivation simultaneously to mathematics learning outcomes is 30.7%, while 69.3% is influenced by other factors not examined by the researchers in this study.